Pedagogical strategies to teach neurodivergent students in the english language classroom - Pereira Chaves, Masiel (2021)
The term neurodiversity can be explained as the distingsition to those people whose neurological characteristics are different from what is considered standard or typical. The purpose of the paper is to help teachers find ways to implement pedagogical strategies to teach Neurological students as well as Neorotypical students. The goal behind these strategies is to help create a safe and understanding environment inside the classroom for neurodivergent students. Also, implementing these practices aims to diminish the alienation of students with ADHD, Autism, dyslexia, etc. Even the smallest changes in the way you teach can impact the students’ life for the better and make the difference between succeeding in learning a second language or giving up in the process entirely.